Biomechanical analysis of the closed reduction internal fixation with cannulated screw of femoral neck fractures - Wang, Jian-Guang (Medicine (Baltimore), 2021)
The influencing factors in closed reduction internal fixation with cannulated screw of femoral neck fractures have not been well investigated. This study evaluated these factors in patients with femoral neck fractures. Fifty-seven patients (36 males and 21 females) diagnosed with femoral neck fracture with the average age of 52.44 ± 15.04 years who underwent closed reduction internal fixation with cannulated screw were included in this study. Data were collected through case report reviews, phone call follow-ups, and outpatient follow-ups to evaluate pre- and postoperative radiograph images. Statistical analysis was performed using Garden classification, binary and multinomial logistic regression analysis by including factors such as patient's age, gender, fracture type, time to fixation, reduction quality, functional recovery period, removal of cannulated screw, and preoperative traction. Logistic regression analysis revealed that age and reduction quality was statistically significant (P < .05) to clinical outcome and other factors were not statistically significant. The main factors affecting clinical outcomes were functional recovery and reduction quality. The biomechanical effects of fixation provide a good foundation for fracture healing. Patient's conditions should be carefully evaluated before selecting reduction procedures to reach an optimal surgical outcome.